GlutenSpA trial: protocol for a randomised double-blind placebo-controlled trial of the impact of a gluten-free diet on quality of life in patients with axial spondyloarthritis - Maxime Dougados; Martin Soubrier; Jacques Morel; Thierry Schaeverbeke; Philippe Gaudin; Marion Couderc; Thierry Thomas; Roland Chapurlat (BMJ Open)
Introduction Subclinical intestinal inflammation and gut dysbiosis have been reported in patients with spondyloarthritis (SpA). In common practice, rheumatologists are increasingly confronted with patients with inflammatory rheumatism who are on gluten-free diets (GFDs), despite the lack of reliable data from controlled studies. This study aims to determine the impact of a GFD on the quality of life of patients with axial SpA.Methods and analysis The GlutenSpA study is a 24-week, randomised, double-blinded, placebo-controlled, multicentre trial. Patients with axial SpA (n=200) will follow a 16-week GFD and be randomly assigned (1:1) to an experimental or control arm. In the experimental arm with receive at least 6 gluten-free breads per day + 200 g of gluten-free penne pasta per week + 6 rice flavour capsules per day. The control arm will receive at least 6 gluten-containing breads per day + 200 g of gluten-containing penne pasta per week + 6 vital gluten-containing capsules per day. The primary end-point is the variation in Assessment of SpondyloArthritis International Society—Health Index (ASAS-HI) questionnaire between week 16 and baseline. A second open-label period of 8 weeks will follow the intervention period, during which the patient will be free to decide whether they will follow the GFD. The secondary outcomes comprise several patient-reported outcomes (SpA activity (Bath Ankylosing Spondylitis Disease Activity Index)), fatigue (Functional Assessment of Chronic Illness Therapy), depression (Hospital Anxiety and Depression Scale), functional disability index (Bath Ankylosing Spondylitis Functional Index)), variations in body mass index and Homeostasis Model Assessment Index and variations in the abundance and type of bacterial species found in the gut microbiota for a subgroup of patients (n=40). The data will be analysed using the intention-to-treat principle.The regional ethics committee (CPP Nord-ouest IV) has approved the study (IDRCB 2018-A00309-46). The results of the trial will be submitted for publication in peer-reviewed journals. The authors have no relationship that may have influenced the submitted work.Trial registration number NCT04274374.